Non pharmacological treatment and its action on the skeletal musculature of elderly with sarcopenia - Ubencenlao Moreno Peña; Clara Esther Martínez Manrique; Clemente Couso-Seoane; Ana de la Caridad Román Montoya (Centro Provincial de Información de Ciencias Médicas, 2022)
Sarcopenia is a geriatric syndrome characterized by the widespread and progressive loss of the skeletal muscular mass and decrease of the muscular force and physical performance. In this respect, the non-pharmacological treatment is of great importance due to its action in the skeletal musculature. In this work the fundamental elements to apply this therapy in elderly are specified whose clinical evaluation includes, among others, the valuation of chronic and acute comorbidities and of their physical functionality by means of the Katz index and the Lawton and Brody scale, the volume of planned physical activity and the diagnosis of the sarcopenia phases by the condition of the skeletal muscular mass, according to the European Working Group on Sarcopenia in Older People. Programs of force and resistance exercises corroborated in meta-analysis are also suggested, with an established duration, frequency and intensity, to strengthen the skeletal musculature and its action on the pathophysiological changes, in order to achieve the muscular adaptation and improve the physical functionality; with it, falls and fractures are prevented in the elderly with sarcopenia and improve their life quality.